2012
DOI: 10.2466/17.13.21.pr0.111.4.165-172
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Sex of Firstborn Child among Primiparous Turkish Women

Abstract: Sex of the baby is an important fantasy object for pregnant women. The objective of this study was to assess the preferences of women for their infants' sex. In this study, 99 primiparous women were included, and accordance of their desires with the newborns' actual sex and feelings about it were examined. All of the mothers were newly delivered and had healthy newborns (53 girls, 46 boys). Before birth, 49 (49.5%) mothers prefered to have a daughter, 25 (25.3%) mothers prefered to have a son, and 25 (25.3%) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
8
2
1
Order By: Relevance
“…Another result of the study was that having a baby of the desired gender was not significantly correlated with the gender of the baby, the nature of the pregnancy as being planned or unplanned, the mode of delivery or the amount of weight gained during pregnancy ( P > 0.05). Similarly, another study did not find a significant correlation between gender preference and the nature of the pregnancy as being planned or unplanned . Although they are not directly comparable with to present this study, several studies in the literature did not find a significant correlation between the gender of the baby and the nature of the pregnancy as being planned or unplanned or the mode of delivery .…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Another result of the study was that having a baby of the desired gender was not significantly correlated with the gender of the baby, the nature of the pregnancy as being planned or unplanned, the mode of delivery or the amount of weight gained during pregnancy ( P > 0.05). Similarly, another study did not find a significant correlation between gender preference and the nature of the pregnancy as being planned or unplanned . Although they are not directly comparable with to present this study, several studies in the literature did not find a significant correlation between the gender of the baby and the nature of the pregnancy as being planned or unplanned or the mode of delivery .…”
Section: Discussioncontrasting
confidence: 82%
“…Gender preference has been dealt with in a number of studies with different perspectives. Gender preference may change depending on the country and culture, or even depending on the region of the country . Another study reported that 55.6% of the participants in their study had a gender preference, whereas only 10.7% of the pregnant women in another study considered the gender of the baby to be important .…”
Section: Discussionmentioning
confidence: 95%
“…All the countries in the review had similar socio-economic conditions and family policies. 8 Individual studies from UK, and Turkey have also reported a strong preference for daughters 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…The pregnant women expressed no preference or preference of one of the gender of their fetuses were seen in various studies. [5][6][7] The studies from western countriesshowed preference of the pregnant women to have a girl, 8 and men's desire to have a son as their first child.…”
Section: Introductionmentioning
confidence: 99%